2016
DOI: 10.1007/s10973-016-5602-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of thermal properties of natural rubber nanocomposites functionalized by nickel–zinc ferrite and potassium strontium niobate nanopowders

Abstract: Several composites and nanocomposites based on a polymeric matrix and ceramic fillers are being pursued for use as multifunctional and innovative materials. Nevertheless, there is a series of challenges to be solved in this area such as the understanding of the role of interfaces and the synergy between matrix and fillers. In this work, vulcanized natural rubber nanocomposites were prepared with different concentrations of two kinds of ceramic nanoparticles, potassium strontium niobate (KSr 2 Nb 5 O 15 or KSN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…The three‐dimensional (3D) infrared spectra have three axes which correspond to wavenumber (axis x ), temperature (axis y ), and absorbance values (axis z ). In this sense, we observed that 3D infrared spectra of the samples with and without QDs are similar and the vibrational frequencies of those spectra are associated with the thermal degradation of rubber according to previous publications, therefore the IR bands from the samples could correspond to gases from the degradation of the polyisoprene. Here, if we select IR spectra at 354 °C from 3D FTIR and the gases released from the RFs and RF/QDs, it is possible to observe clearly the IR bands associated with the rubber degradation and no IR bands related to QDs.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The three‐dimensional (3D) infrared spectra have three axes which correspond to wavenumber (axis x ), temperature (axis y ), and absorbance values (axis z ). In this sense, we observed that 3D infrared spectra of the samples with and without QDs are similar and the vibrational frequencies of those spectra are associated with the thermal degradation of rubber according to previous publications, therefore the IR bands from the samples could correspond to gases from the degradation of the polyisoprene. Here, if we select IR spectra at 354 °C from 3D FTIR and the gases released from the RFs and RF/QDs, it is possible to observe clearly the IR bands associated with the rubber degradation and no IR bands related to QDs.…”
Section: Resultssupporting
confidence: 78%
“…In this sense, we observed that 3D infrared spectra of the samples with and without QDs are similar and the vibrational frequencies of those spectra are associated with the thermal degradation of rubber according to previous publications, therefore the IR bands from the samples could correspond to gases from the degradation of the polyisoprene. Here, if we select IR spectra at 354 °C from 3D FTIR and the gases released from the RFs and RF/QDs, it is possible to observe clearly the IR bands associated with the rubber degradation and no IR bands related to QDs. Vibrational frequencies shown in Figure correspond to asymmetric stretching of CH 2 at 2927 cm −1 , symmetric stretching of CH 2 at 2869 cm −1 , stretching of CC at 1635 cm −1 , angular deformation CH 2 at 1455 cm −1 , angular deformation CH 3 at 1369 cm −1 , and CH wagging in the CH 3 883 cm −1 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The maximum degradation rates of all vulcanizates were located at around 373 °C, which indicated that the elastomeric properties of the vulcanized NR were maintained in the composites. A small shoulder with low intensity, marked by a red arrow, at around 420 °C was confirmed for all materials, which was assigned to the different degradation temperatures for the constituents of NR . In this study, the thermal stability temperature ( T s ) of the materials was measured by the temperature when 1% of mass loss occurred.…”
Section: Resultsmentioning
confidence: 98%
“…The composites with various filler content exhibit similar thermal gravimetric curves. The fast mass loss between 300 and 490 °C was attributed to the thermal degradation of polyisoprene, dipentene, and p ‐menthene . The maximum degradation rates of all vulcanizates were located at around 373 °C, which indicated that the elastomeric properties of the vulcanized NR were maintained in the composites.…”
Section: Resultsmentioning
confidence: 99%